KECEMASAN DAN KUALITAS TIDUR USIA DEWASA DI PANDEMI COVID-19 - Tobing, Duma Lumban; Haryani, Ariyana Pramitha (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
ABSTRACT The Covid-19 pandemic is a new disease that is endemic throughout the world and is spreading very quickly. As a result, many people suffer from excessive anxiety which affects the quality of their sleep. The purpose of this study was to identify the relationship between people's anxiety levels and sleep quality during the Covid-19 pandemic. This study used a cross-sectional correlation model to determine the relationship between two variables, namely the independent variable anxiety and the dependent variable sleep quality during the Covid-19 pandemic. Data collection was carried out by direct observation using the Hamilton Anxiety Rating Scale Instrument and the Pittsburgh Sleep Quality Index. The sample in this study consisted of 103 respondents who were taken using a purposive sampling technique. The data analysis used was univariate and bivariate analysis using the chi-square test. The results showed that there was a relationship between general anxiety and sleep quality during the Covid-19 pandemic (p-value = 0.000). This research will help broaden our knowledge and skills to manage stress and improve sleep quality. Keywords: COVID-19, Anxiety, Sleep Quality